PERFORMA BUDIDAYA IKAN LELE SANGKURIANG (Clarias gariepinus) SISTEM BIOFLOK DENGAN INTERVENSI GRADING - Novira Nanda Tasyah; Mugi Mulyono; Moch Farchan; Amyda Suryati Panjaitan; Effi Aftiani Thaib (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2020)
Sangkuriang catfish is a freshwater consumption fish that has a pretty good profit. The application of biofloc technology in catfish farming increases the cost of feed up to 300 (20% of the total production cost, and my jugaldenaku)). The purpose of the study was to determine the application of interventions and measurement of aquaculture performance. FCR 0.8 and SR 88.3%. The application of intervention by grading began at Daily of Culture (DOC) 35 then every 2 weeks until harvest. The percentage of oversized harvest size in non-intervention ponds was 28.9% while in intervention pools 5.3% income loss can be increased from 1,036,600 IDR to only 78,000 IDR.